Neurosurgical Review - Sure, Ulrich; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The goal of Neurosurgical Review is to provide a forum for comprehensive reviews on current issues in neurosurgery. Each issue contains up to three reviews, reflecting all important aspects of one topic (a disease or a surgical approach). By providing comprehensive coverage of one topic per issue, Neurosurgical Review combines the topicality of professional journals with the in-depth treatment of a monograph. Original papers of high quality are also welcome.
Keywords: Neurosurgery; Neurosurgery